Questionner l’efficacité de la gouvernance d’une AMP : le cas de Natura 2000 en mer - Jean-Eudes Beuret; Ludovic Martel; Anne Cadoret; Frédérique Chlous; Julie Delannoy; Marie Lesueur; Christelle Noirot; Hélène Rey-Valette; Lucille Ritschard; Paul Sauboua (VertigO)
This article is focused on the governance of one type of Marine Protected Areas, namely Natura 2000 at sea. The aim is to identify what is determinant for the effectiveness of their governance. From a database of 158 sites located in Hexagonal France, 20 were used for comparative case-studies. The analysis of the database shows that despite an identical national framework, it is in fact implemented very differently according to the diversity of maritime frontage, regions and sites. To understand this diversity, we describe four discriminant factors: the overlapping of the Natura 2000 area within another territorial management zone, the governance temporalities (before or after the management plan), local proximities (pre-existing or to be created), the geographical location of the site (coastal or offshore). Then we analyze the effects and impacts of governance, according to their characteristics. Their added benefits are described (direct effect, rebound-effect, resources, actions and coordination), revealing that their effectiveness is nonetheless conditional. The effectiveness and quality of the governance are then characterized according to the objectives of Natura 2000 at sea and some improvements are suggested.